P14.20 Anxiety level in a prospective cohort of newly diagnosed glioblastoma patients: preliminary results from the IMAGE study. (6th September 2019) - Maillet, D; Narme, P; Menard, V; Larrieu, M; Sahel, K; Belin, C; Carpentier, A
Abstract: BACKGROUND: Quality of life (QoL) is an important area of clinical neuro-oncology, especially in glioblastoma patients. Although previous studies showed an association between QoL and anxiety, few studies have focused on the anxiety level throughout the disease progression (Bunevicius et al., 2017; Kilbride et al., 2007). Underestimating anxiety may have several consequences: a low treatment compliance, exacerbation of somatic symptoms or side effects of treatment, difficulties with understanding medical information and lower cooperation with the medical staff (Spencer, 2010). In the present study, we aimed assessing the current state of anxiety in a prospective cohort of patients treated for glioblastoma. We also investigated potential correlations with other clinical and psychological variables to better understand determinants of anxiety in this population. MATERIAL AND METHODS: At the beginning of their cycle of temozolomide cure and after radio-chemotherapy, 30 patients with glioblastoma were included. Inclusion criteria were: Karnofsky index (IK) ≥ 70% and absence of cognitive disorder that could interfere with the completion of questionnaires. The characteristics of patients were as follows: mean age of 56.6 years ± 12.5 (70% were more than 50 years old); 20% were women; 50% had a university degree and IK of 87% ± 5. Anxiety level was assessed using the State-Trait Anxiety Inventory. This scale consists of 40 items on a self-report basis measuring how patients feel right now ("state") and how they generally feel ("trait"). We also assessed (i) QoL using the Cancer Quality of Life Questionnaire 30 and the Brain Cancer Module-20; (ii) the presence of depressive symptoms using the Hospital Anxiety and Depression Scale; (iii) the self-esteem using the Rosenberg self-esteem scale and (iv) memory complains using the Prospective and Retrospective Memory Questionnaire. RESULTS: The preliminary results showed that - at baseline - 21% of our sample reported high levels of anxiety. Correlation analyses showed that state anxiety was correlated with trait anxiety (rho=0.799, p< .001), QoL (rho=0.678, p< .001), level of self-esteem (rho=-0.514, p=0.004) and memory complains (rho=0.618, p< .001). Any correlation was found with age, education level, lesional lateralization or depressive symptoms. Women had higher state anxiety scores than men (t(27)=-2.4, p=0.02). CONCLUSION: These preliminary results suggest that higher current state of anxiety is associated with lower QoL and lower self-esteem, regardless the presence of depressive symptoms, age, education level or lesional lateralization. Anxiety level at the follow-up (4 and 6 months after the baseline) and determinants of its progression will also be presented and might help health professionals to understand patients' experience and better meet their needs.